How Disability and Other Socio-Economic Factors Matter to Children?s Socio-Emotional Outcomes: Results from a Longitudinal Study Conducted in Ireland - Curry, Philip; Garcia Iriarte, Edurne; Gilligan, Robert (My University, 2020)
Children with disabilities experience significantly poorer socio-emotional outcomes than their peers without disabilities. However, research evidence is scarce about children with both disability and migration background, the group which this study aimed to investigate using data from a national longitudinal study. Secondary data analyses were conducted on a sample of 7,290children (weighted with missing values imputed). Significant differences in socio-emotional outcomes were found in relation to impairment status but not in relation to migration. Having an impairment and activity limitation significantly increased the likelihood of experiencing poorer socio-emotional outcomes over time. Our findings highlight a higher risk of socio-emotional problems among children with disabilities, especially among children from lower income backgrounds and with parents with lower educational attainment. These findings clearly require policy development on two fronts: to raise professional and community awareness on these issues and to strengthen the capacity of health, education and social care systems to support schools, families, and communities.
PUBLISHED
https://link.springer.com/article/10.1007/s12187-020-09768-y?wt_mc=Internal.Event.1.SEM.ArticleAuthorOnlineFirst
Keywords: Disability; Migration; Children; Socio-emotional outcomes; Strengths and Difficulties Questionnaire; Growing Up in Ireland; Inclusive Society; Children, health and disability; Disability